2019
DOI: 10.1126/science.aau1361
|View full text |Cite
|
Sign up to set email alerts
|

Differential soil fungus accumulation and density dependence of trees in a subtropical forest

Abstract: The mechanisms underlying interspecific variation in conspecific negative density dependence (CNDD) are poorly understood. Using a multilevel modeling approach, we combined long-term seedling demographic data from a subtropical forest plot with soil fungal community data by means of DNA sequencing to address the feedback of various guilds of soil fungi on the density dependence of trees. We show that mycorrhizal type mediates tree neighborhood interactions at the community level, and much of the interspecific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
153
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(169 citation statements)
references
References 71 publications
14
153
0
2
Order By: Relevance
“…Early arriving pathogens can reduce susceptibility to subsequent infections by inducing defenses 91,92 . Microbial mutualists, such as mycorrhizae, can also protect plants from pathogens, 93–95 as well as influence feedbacks 23,96 . In feedback models and experiments to date, immunological aspects of feedbacks are typically subsumed in the fitness effects that the microbiome has on its host 90 .…”
Section: Dilution Effect: Aligning Epidemiological and Feedback Framementioning
confidence: 99%
“…Early arriving pathogens can reduce susceptibility to subsequent infections by inducing defenses 91,92 . Microbial mutualists, such as mycorrhizae, can also protect plants from pathogens, 93–95 as well as influence feedbacks 23,96 . In feedback models and experiments to date, immunological aspects of feedbacks are typically subsumed in the fitness effects that the microbiome has on its host 90 .…”
Section: Dilution Effect: Aligning Epidemiological and Feedback Framementioning
confidence: 99%
“…A growing number of studies have employed approaches that provide direct or indirect evidence for the role of insect herbivores and microbial pathogens as drivers of CNDD. These approaches include measurement of detectable herbivore or pathogen damage on plants (e.g., Gilbert et al, 1994;Norghauer et al, 2006), plant-soil feedback experiments (e.g., Mangan et al, 2010), use of genetic methods to identify soil pathogens (e.g., Chen et al, 2019), quantifying neighborhood similarity in plant defenses (e.g., Forrister et al, 2019), and in situ manipulation of enemies using mesh exclosures, fungicides, and/or insecticides (e.g., Bell et al, 2006;Swamy & Terborgh, 2010;Bagchi et al, 2014). Studies using these approaches have demonstrated that natural enemies play an important role in driving tropical tree recruitment and potentially contributing to tropical tree diversity.…”
Section: Effectsmentioning
confidence: 99%
“…密度制约强度随生境和季节的变化而变化, 在某些 森林中甚至比生境过滤的作用更强 [3] . 亚热带森林病 原菌积累率高的树种对同种植物密度的依赖性较强, 而同种密度依赖性低的树种对外生菌根真菌的积累率 较高 [7] . 温带森林中同种幼苗的存活和更新与真菌和 植食昆虫密切相关 [8] .…”
Section: 中国森林生物多样性监测网络有力支撑生物群落 维持机制研究unclassified